2012
DOI: 10.1016/j.crhy.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Quick measurements of energy efficiency of buildings

Abstract: Efficacité énergétique des bâtiments Mesures thermodynamique rapide États transitoires Capacité calorifique Coefficient de fuite thermiqueIn this study, we propose a way to develop rapid measurements of the energy efficiency of buildings. We show that measuring transient states during the heating and free cooling of an empty low-consumption house can lead to a rather good estimate of the total heat loss coefficient K and of the apparent heat capacity C of the building. These measurements can be made typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…Andrews [45] provides a useful review of the variation seen in successive short term dynamic measurements-with consistent results generally achieved once weather corrections are applied. However, Liu and Claridge [46] noted the importance of understanding the thermal history of a dwelling prior to measurements in order to avoid systematic bias and Andrews [43] concluded that that further tests on a wider range of dwellings was needed, a statement that still holds true, particularly concerning heavyweight and highly glazed dwellings. Recent work has looked to develop the application of dynamic test sequences and analysis (e.g., ARX, ARMAX, state space models) from single components to whole building characterisation [47,48].…”
Section: Alternative Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrews [45] provides a useful review of the variation seen in successive short term dynamic measurements-with consistent results generally achieved once weather corrections are applied. However, Liu and Claridge [46] noted the importance of understanding the thermal history of a dwelling prior to measurements in order to avoid systematic bias and Andrews [43] concluded that that further tests on a wider range of dwellings was needed, a statement that still holds true, particularly concerning heavyweight and highly glazed dwellings. Recent work has looked to develop the application of dynamic test sequences and analysis (e.g., ARX, ARMAX, state space models) from single components to whole building characterisation [47,48].…”
Section: Alternative Methodsmentioning
confidence: 99%
“…These methods can often elicit results in shorter time frames than steady state approaches, offering obvious advantages over the longer, steady state co-heating test. For example, the PSTAR method used a 48 or 72 h test sequence [42], with similar recent dynamic methods aiming to achieve results in similar time periods [43,44]. Andrews [45] provides a useful review of the variation seen in successive short term dynamic measurements-with consistent results generally achieved once weather corrections are applied.…”
Section: Alternative Methodsmentioning
confidence: 99%
“…A small number of dynamic aggregate test methods have been devised. These include: ISABELE [18], the Primary and Secondary Terms-Analysis and Renormalization (PSTAR) method [19][20][21] and the Quick U-value of Buildings (QUB) method [22]. Although the dynamic methods offer the advantage of much shorter test durations than is required by the quasi steady-state coheating test method, the analysis of the data obtained from these test methods tends to be significantly more complex.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic whole house heat loss test methods exist that are far shorter in duration than the coheating test. These include: ISABELE (Bouchié et al [23]), the Quick U-value of Buildings (QUB) method (Mangematin et al [24]) and the Primary and Secondary Terms-Analysis and Renormalization (PSTAR) method (Subbaro [25], Subbaro et al [26]). However, the nature of the HLC estimation obtained by PSTAR was questioned when compared with that measured by a coheating test on the same dwelling (Palmer et al [27]).…”
Section: Introductionmentioning
confidence: 99%